2017
DOI: 10.1002/lary.26652
|View full text |Cite
|
Sign up to set email alerts
|

How does radioactive iodine affect the nose?

Abstract: 4. Laryngoscope, 127:2698-2702, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Server et al . 12 reviewed the effect of radioactive iodine therapy on nasal mucosa and nasal functions. The study included 41 patients (31 females and 10 males) who had received radioactive iodine therapy following papillary thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Server et al . 12 reviewed the effect of radioactive iodine therapy on nasal mucosa and nasal functions. The study included 41 patients (31 females and 10 males) who had received radioactive iodine therapy following papillary thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that radioactive iodine accumulation in the nose is normal and higher than in the mouth and parotid gland, 10 nasal complications have been neglected and only a limited number of studies have been published. [11][12][13] Those studies concluded that radioactive iodine caused loss of smell in patients, but the effect of dose was not investigated. This study aimed to determine whether the short-and long-term adverse effects on smell, taste and nose function are dependent on radioactive iodine dose.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with RAI can produce early and late complications. The common early complications include swelling and discomfort in the neck, xerostomia, dry eye, abnormalities of taste and smell, dysphagia, nausea, vomiting, bone marrow suppression [90], gonadal damage (hypospermia or temporary amenorrhea/oligomenorrhea), nasal dryness and obstruction, and nasolacrimal obstruction [91][92][93][94][95][96]. The late complications include permanent salivary gland dysfunction, leukemia and secondary malignancy, pulmonary fibrosis, fertility problems [97][98][99][100][101][102].…”
Section: Effect Of Rai Treatment On Parathyroid Function For Dtc Patientsmentioning
confidence: 99%